2018
DOI: 10.5430/jnep.v8n9p25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excessive internet use in Saudi and Egyptian teenagers’ health: Comparative study

Abstract: Using of the internet today is a growing part of any society. Teenagers are the most users of the internet at their home and/or school. Therefore, it changes their daily lives in terms of physical, social, and psychological status that may exaggerated to be an internet addiction disorder or a physical problem. The aim of the study was to recognize the effects of excessive internet use in Saudi and Egyptian teenagers' health. The design used to conduct the present study was a descriptive correlation design, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…(10) Moreover, the results of the current study are higher than results of Nafee et al, who assessed IA among teenagers in Saudi Arabia and in Egypt, and found that 47.7%, 45.3%, and 0.9% of the Saudi teenagers were mild, moderate and severe Internet addicts compared to 44.2%, 46.3% and 0.3% of the Egyptian teenagers. (21) Although the results of the current study are comparable to the results of Al-Shdayfat et al, who reported that 65% of Jordan adolescents were Internet addicts. (13) Comparing prevalence of IA is difficult due to the heterogeneity of assessment instruments, using varying samples and designs in the conducted studies and varying target populations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…(10) Moreover, the results of the current study are higher than results of Nafee et al, who assessed IA among teenagers in Saudi Arabia and in Egypt, and found that 47.7%, 45.3%, and 0.9% of the Saudi teenagers were mild, moderate and severe Internet addicts compared to 44.2%, 46.3% and 0.3% of the Egyptian teenagers. (21) Although the results of the current study are comparable to the results of Al-Shdayfat et al, who reported that 65% of Jordan adolescents were Internet addicts. (13) Comparing prevalence of IA is difficult due to the heterogeneity of assessment instruments, using varying samples and designs in the conducted studies and varying target populations.…”
Section: Discussionsupporting
confidence: 84%
“…(14,17,18) Although several studies assessed the prevalence of IA and its psychological hazards among Egyptian University students (19,20) , few studies assessed IA among high school students. (2,10,21) Studies conducted in other countries proposed that younger age groups became more engaged in Internet-related activities which necessitates assessing IA among these age groups in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these studies were conducted in educational settings, and therefore did not represent the level of IA among youths who dropped out Prevalence 1 0.8 0.6 0.4 0.2 0 Study Alshehri et al, 2015Al-hantoushi et al, 2014Taha et al, 2019Bener et al, 2013Barayan et al, 2018 Overall Q=1467.29, p=0.00, I2=99% H.U. Khan et al, 2018Nafee et al, 2018Abdel-Salam et al, 2019Hasan et al, 2019 H.U. Khan et al, 2017 Prev (Li, Garland, & Howard, 2014;Shek, Zhu, & Dou, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An overwhelming percentage of the population in these countries has internet access (Saudi Arabia 5 93%, Qatar and Kuwait 5100%) (The World Bank, 2019). The available data show that the prevalence of IA in GCC countries ranges anywhere from 4% to 82.6% (Abdel-Salam, Alrowaili, Albedaiwi, Alessa, & Alfayyadh, 2019;Alhantoushi & Alabdullateef, 2014;Alshehri, Azahrani, & Alotaibi, 2015;Barayan, Al Dabal, Abdelwahab, Shafey, & Al Omar, 2018;Bener & Bhugra, 2013;Hasan & Jaber, 2019;Khan & Awan, 2017;Khan & Gadhoum, 2018;Nafee, Mohammed, & Al-Hamdan, 2018;Taha, Shehzad, Alamro, & Wadi, 2019) The considerable wealth and access to advanced technology contribute to such high estimates. Additionally, variation in the definition of the problem (e.g., problematic, excessive, addictive use of internet), differences in the sample compositions (e.g., age and gender distribution), and use of disparate tools for outcome assessment may have contributed to the variation in prevalence estimates.…”
Section: Introductionmentioning
confidence: 99%
“…What are the remedies that parents follow to reduce excessive use of online devices? Nafee, Mohammed, and Al-Hamdan (2018) have shown that 86.6% of the Kingdom of Saudi Arabia (KSA) teenagers used the internet daily compared to 69.6% in the Arab Republic of Egypt (ARE). Regarding internet addiction, in teenagers, 0.9% were severe, 45.3% moderate and 47.7% mild compared to 0.3%, 46.3% and 44.2% in ARE, 67.3% of KSA teenagers have musculoskeletal pain with internet usage compared to 74.3% in ARE teenagers.…”
Section: Introductionmentioning
confidence: 99%